Home safety assessment and modification to reduce injurious falls in community-dwelling older adults: cost-utility and equity analysis. Issue 6 (24th May 2016) - Pega, Frank; Kvizhinadze, Giorgi; Blakely, Tony; Atkinson, June; Wilson, Nick
Abstract : Background: This study aimed to improve on previous modelling work to determine the health gain, cost-utility and health equity impacts from home safety assessment and modification (HSAM) for reducing injurious falls in older people. Methods: The model was a Markov macrosimulation one that estimated quality-adjusted life-years (QALYs) gained. The setting was a country with detailed epidemiological and cost data (New Zealand (NZ)) for 2011. A health system perspective was taken and a discount rate of 3% was used (for both health gain and costs). Intervention effectiveness estimates came from a Cochrane systematic review and NZ-specific intervention costs were from a randomised controlled trial. Results: In the 65 years and above age group, the HSAM programme cost a total of US$98 million (95% uncertainty interval (UI) US$65 to US$139 million) to implement nationally and the accrued net health system costs were US$74 million (95% UI: cost saving to US$132 million). Health gains were 34 000 QALYs (95% UI: 5000 to 65 000). The incremental cost-effectiveness ratio (ICER) was US$6000 (95% UI: cost saving to US$13 000), suggesting that HSAM is highly cost-effective. Targeting HSAM only to older people with previous injurious falls and to older people aged 75 years and above were also cost-effective (ICERs=US$1000 and US$11 000, respectively). There was no evidence for differential cost-effectiveness by gender or by ethnicity (Indigenous New Zealanders: Māori vs non-Māori). Conclusions: As per other studies, this modelling study indicates that the provision of an HSAM intervention produces considerable health gain and is highly cost-effective among older people. Targeting this intervention to older people with previous injurious falls is a promising initial approach before any scale up. Trial registration number: ACTRN12609000779279.